High-entropy doped titanium niobium oxide and preparation method and application thereof

By introducing a variety of metal elements into the titanium niobate material to form a high-entropy doped structure and combining with the conductive polymer cladding layer, the problem of low conductivity of titanium niobate in sodium ion batteries is solved, and the performance of highly efficient sodium ion battery negative electrode material is achieved.

CN119812295AActive Publication Date: 2025-04-11BYD CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411669895.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-04-11
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing titanium niobate materials have low electron and ion conductivity in sodium ion batteries, limiting their development in electrochemical energy storage applications.

Method used

By introducing a variety of metal elements, high-entropy doped titanium niobium oxides are formed, their structure is optimized, ion transport capacity is improved, and electron conduction capacity is improved through conductive polymer cladding.

Benefits of technology

It achieves high specific capacity, high magnification characteristics and excellent cycling performance, and is suitable for sodium ion battery negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812295A_ABST
    Figure CN119812295A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a high-entropy doped titanium niobium oxide and a preparation method and application thereof.The high-entropy doped titanium niobium oxide comprises a compound shown in the formula 1: TiNb < 24-x > M < x > O < 62 >, in the formula 1, M comprises at least five of Re, Mo, W, V, Cr, Cu, Ni, Fe, Co, Cu, Zn, Mn, Sn, Bi, K, Mg, Al, Li, Rb, Cs, Ru, Rh, Pd, Ag, In, Ir and Pb; and x ranges from 0.8 to 1.6. The high-entropy doped titanium niobium oxide can be used as a sodium battery negative electrode material, and has high specific capacity, high magnification characteristic and excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sodium ion batteries, and specifically to high entropy doped titanium niobium oxide and a preparation method and application thereof, and more specifically to high entropy doped titanium niobium oxide and a preparation method thereof, a negative electrode material for sodium ion batteries, a sodium ion battery and an electrical device. Background Art

[0002] Titanium niobate (TiNb 24 O 62 ) materials are considered to be ideal negative electrode materials for lithium-ion batteries due to their excellent performance and high safety. Their higher working potential can effectively prevent the formation of lithium dendrites. However, their low electronic and ionic conductivity limits their further development in electrochemical energy storage applications, especially for sodium ions with larger ionic radius and greater diffusion resistance, whose electronic and ionic conductivity is further reduced. However, since sodium resources are widespread and not geographically restricted, and sodium and lithium have similar electrochemical storage characteristics, sodium-ion batteries have received widespread attention and are considered to be one of the strong competitors of lithium-ion batteries in the fields of large-scale energy storage and low-speed trams. If titanium niobate (TiNb 24 O 62 ) materials can be successfully applied in sodium-ion batteries and will be of great value. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention proposes a high entropy doped titanium niobium oxide that can be effectively used as a sodium battery negative electrode material and a preparation method and application thereof.

[0004] In a first aspect of the present application, a high entropy doped titanium niobium oxide is provided. According to an embodiment of the present application, the high entropy doped titanium niobium oxide comprises a compound shown in Formula 1:

[0005] Tb 24-x M x O 62 Formula 1

[0006] Among them, M includes at least 5 of Re, Mo, W, V, Cr, Cu, Ni, Fe, Co, Cu, Zn, Mn, Sn, Bi, K, Mg, Al, Li, Rb, Cs, Ru, Rh, Pd, Ag, In, Ir and Pb; and x is 0.8 to 1.6.

[0007] According to the high entropy doped titanium niobium oxide of the embodiment of the present application, by introducing a variety of metal elements, with the help of different valence states and ion sizes of the various metal elements, the positions of niobium atoms are randomly replaced, and the high entropy doping configuration and position are regulated by adjusting the temperature and element content, the structure of the titanium niobium oxide is optimized, the ion transport capacity thereof is improved, and the band structure and vacancy concentration are regulated to provide more high active sites. Thus, the high entropy doped titanium niobium oxide can be used as a negative electrode material for sodium electricity, and has high specific capacity, high rate characteristics and excellent cycle performance.

[0008] According to the embodiments of the present application, x can be 0.9 to 1.2. Within the above content range, M can be uniformly doped into the titanium niobium oxide bulk phase, with good uniformity, and is not prone to problems such as agglomeration and segregation, which is conducive to making the high-entropy doped titanium niobium oxide have better sodium storage performance, and when used as a sodium battery negative electrode material, it has a higher specific capacity, higher rate characteristics and better cycle performance.

[0009] According to an embodiment of the present application, M includes at least one element with a highest valence state lower than +5 and at least one element with a highest valence state higher than +5. Specifically, niobium element usually exists in the crystal structure of high entropy doped titanium niobium oxide in the form of +5 valence, and the doping element M partially selects elements with a highest valence state higher than +5 valence, and partially selects elements with a highest valence state lower than +5 valence, which is beneficial to valence balance and the generation of vacancies in the crystal structure, and can effectively regulate the configuration of high entropy doping, thereby being more conducive to ion conduction.

[0010] According to an embodiment of the present application, M includes at least 5 elements in equal moles. Thus, the high entropy doping effect can be better achieved, the ion transport capacity of the high entropy doped titanium niobium oxide can be better improved, and more high active sites can be provided, so that it can well meet the use requirements of the sodium negative electrode material.

[0011] According to an embodiment of the present application, the high entropy doped titanium niobium oxide further includes: a conductive polymer coating layer, which is coated on at least part of the surface of the compound shown in Formula 1. The introduction of a conductive polymer to coat the high entropy doped titanium niobium oxide effectively improves its electronic conductivity and achieves higher structural stability. When it is used as a sodium battery negative electrode material, it can achieve high specific capacity, high rate characteristics and excellent cycle performance.

[0012] According to an embodiment of the present application, the material of the conductive polymer coating layer includes at least one of polyaniline, polypyrrole, and poly (3,4-ethylenedioxythiophene). Therefore, the above polymer has good conductivity, which is beneficial to improve the electronic conductivity and structural stability of high entropy doped titanium niobium oxide, and the material source is wide, easy to obtain, and low in cost. At the same time, it is easy to form a film on the surface of the compound shown in Formula 1 and easy to process.

[0013] According to an embodiment of the present application, the thickness of the coating layer is 0.1 nm to 5 nm, specifically 2 nm; the mass proportion of carbon element in the high entropy doped titanium niobium oxide is 0.2% to 0.8%, specifically 0.4%.

[0014] According to the embodiments of the present application, the high entropy doped titanium niobium oxide has a porous structure, which can greatly accelerate the transmission of sodium ions between particles and crystal domains, and can achieve better electrochemical performance when used as a negative electrode material for sodium ion batteries.

[0015] According to an embodiment of the present application, the porous structure includes mesopores with a pore size of 3 nm to 10 nm, thereby further accelerating the transmission of sodium ions between particles and crystal domains, and achieving better electrochemical performance when used as a negative electrode material for sodium ion batteries.

[0016] According to the embodiment of the present application, the high entropy doped titanium niobium oxide is in the form of microspheres, and the D 50 The particle size is 4μm to 15μm. It has a spherical morphology, which is more conducive to the transmission of sodium ions, and can achieve better electrochemical performance when used as a negative electrode material for sodium ion batteries.

[0017] In a second aspect of the present application, a method for preparing the high entropy doped titanium niobium oxide described above is provided. According to an embodiment of the present application, the method comprises: mixing a carbon source, a titanium source, a niobium source, an M source and a solvent to obtain a mixed solution; subjecting the mixed solution to a hydrothermal reaction to obtain an intermediate; and calcining the intermediate to obtain a compound shown in Formula 1. The method is simple and convenient to operate, has mild conditions, and is easy to implement.

[0018] In some embodiments, the mass ratio of the carbon source, titanium source, niobium source, and M source can be (0.01-10): (10-30): (400-600): (0.01-20), specifically (3-7): (15-25): (450-550): (5-15). Within the above ratio range, high entropy doped titanium niobium oxide has a structure that is more conducive to ion transport, can meet the requirements for use as a sodium ion negative electrode material, can be effectively used as a sodium ion negative electrode material, and improve the performance of sodium ion batteries.

[0019] According to an embodiment of the present application, the carbon source may include at least one of glucose, starch, sucrose, and fructose. This facilitates the formation of a porous structure in high entropy doped titanium niobium oxide, and the material source is wide and the cost is low.

[0020] According to an embodiment of the present application, the titanium source may include at least one of tetrabutyl titanate and titanium isopropoxide. The niobium source may include at least one of niobium pentachloride and niobium ethanol. The M source may include compounds of at least 5 elements of Re, Mo, W, V, Cr, Cu, Ni, Fe, Co, Cu, Zn, Mn, Sn, Bi, K, Mg, Al, Li, Rb, Cs, Ru, Rh, Pd, Ag, In, Ir, and Pb that are soluble in the solvent. In some embodiments, the solvent includes ethanol. Thus, the reaction is facilitated, the material is easily available, and the cost is low.

[0021] According to the embodiment of the present application, the temperature of the hydrothermal reaction may be 100° C. to 200° C., specifically 120° C. to 180° C. Within the above temperature range, the hydrothermal reaction is suitable, the reaction is sufficient, the speed is fast, and there are few side reactions.

[0022] According to the embodiment of the present application, the heating rate of the hydrothermal reaction is 2°C / min to 20°C / min, specifically 5°C / min to 15°C / min. The above heating rate range can make the high entropy doped titanium niobium oxide have a suitable pore size and good uniformity of each doping element.

[0023] According to an embodiment of the present application, the holding time of the hydrothermal reaction is 0.2h to 2h, specifically 0.2h to 1h. The above time range can allow the hydrothermal reaction to proceed fully without wasting time.

[0024] According to an embodiment of the present application, the calcination temperature is 300° C. to 1800° C., specifically 500° C. to 1200° C. In the above temperature range, it is beneficial to obtain a high-entropy doped titanium niobium oxide with a suitable porous structure and high-entropy doping configuration, thereby achieving better sodium ion transport performance.

[0025] According to an embodiment of the present application, the heating rate of the calcination treatment is 10°C / min to 200°C / min, specifically 10°C / min to 200°C / min. Within the above heating rate range, it is beneficial to obtain high entropy doped titanium niobium oxide with good uniformity of doping elements.

[0026] According to the embodiments of the present application, the holding time of the calcination treatment is 0.1 to 2 hours, specifically 0.3 to 1 hour. Within the above temperature range, the reaction can be fully carried out without wasting time due to too long a time, which is conducive to improving efficiency.

[0027] According to an embodiment of the present application, the method further comprises: forming a conductive polymer coating layer on the surface of the compound represented by Formula 1. Introducing a conductive polymer to coat high entropy doped titanium niobium oxide can effectively improve the electron conductivity and achieve higher structural stability. As a negative electrode material for sodium ion batteries, it can achieve higher specific capacity, higher rate characteristics and excellent cycle performance.

[0028] According to an embodiment of the present application, forming a conductive polymer coating layer may include: immersing the compound represented by Formula 1 in a conductive polymer monomer aqueous solution to obtain a dispersion; adding an initiator to the dispersion, and continuously stirring to polymerize the conductive polymer monomer to form the conductive polymer coating layer on the surface of the compound represented by Formula 1. Specifically, the conductive polymer monomer may undergo a polymerization reaction under the initiation of the initiator and be coated on the surface of the compound represented by Formula 1.

[0029] According to an embodiment of the present application, the concentration of the conductive polymer monomer aqueous solution is 0.1M to 1M, specifically 0.2M to 0.6M. Thus, a conductive polymer coating layer with a better coating effect can be obtained, which can effectively improve the electronic conductivity and achieve higher structural stability.

[0030] According to the embodiment of the present application, the polymerization reaction time is 0.5h to 2h, specifically 1h to 1.5h. Within the above time range, a conductive polymer coating layer with better effect can be obtained.

[0031] In a third aspect of the present application, a negative electrode material for a sodium ion battery is provided. According to an embodiment of the present application, the negative electrode material for a sodium ion battery comprises the high entropy doped titanium niobium oxide described above, or the high entropy doped titanium niobium oxide prepared by the method described above. Using high entropy doped titanium niobium oxide as a negative electrode material for a sodium ion battery can achieve high specific capacity, high rate characteristics and excellent cycle performance.

[0032] In a fourth aspect of the present application, a sodium ion battery is provided. According to an embodiment of the present application, the sodium ion battery comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode material, and the negative electrode material comprises the sodium ion battery negative electrode material described above. The sodium ion battery has a high specific capacity, a high rate characteristic and excellent cycle performance.

[0033] In a fifth aspect of the present application, an electric device is provided. According to an embodiment of the present application, the electric device includes the sodium ion battery described above. The electric device has all the features and advantages of the sodium ion battery described above, which will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1This is a SEM photograph of the high entropy doped titanium niobium oxide material obtained in Example 1 of the present application.

[0035] Figure 2 This is a SEM photograph of the high entropy doped titanium niobium oxide material obtained in Example 8 of the present application. DETAILED DESCRIPTION

[0036] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0037] This application is completed based on the following discoveries and understandings of the inventors:

[0038] The inventors have found that the titanium niobate material in the related art has a distinct bulk structure, which limits the diffusion of sodium ions. In order to improve the sodium storage capacity of titanium niobate, it is crucial to further optimize the structure. At the same time, the inventors noticed that high-entropy materials have a simple crystal structure of a multi-component mixture (usually five or more equimolar elements) and a single-phase solid solution, which provides huge compositional possibilities for customizing target functions.

[0039] In view of this, in a first aspect of the present application, a high entropy doped titanium niobium oxide is provided. According to an embodiment of the present application, the high entropy doped titanium niobium oxide comprises a compound shown in Formula 1:

[0040] TnB 24-x M x O 62 Formula 1

[0041] Among them, M includes at least 5 of Re, Mo, W, V, Cr, Cu, Ni, Fe, Co, Cu, Zn, Mn, Sn, Bi, K, Mg, Al, Li, Rb, Cs, Ru, Rh, Pd, Ag, In, Ir and Pb; and x is 0.8 to 1.6.

[0042] According to the high entropy doped titanium niobium oxide of the embodiment of the present application, by introducing a variety of metal elements, with the help of different valence states and ion sizes of the various metal elements, the positions of niobium atoms are randomly replaced, and the high entropy doping configuration and position are regulated by adjusting the temperature and element content, the structure of the titanium niobium oxide is optimized, the ion transport capacity thereof is improved, and the band structure and vacancy concentration are regulated to provide more high active sites. Thus, the high entropy doped titanium niobium oxide can be used as a negative electrode material for sodium electricity, and has high specific capacity, high rate characteristics and excellent cycle performance.

[0043] According to the embodiments of the present application, x can be 0.9 to 1.2, such as 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, etc. Within the above content range, M can be uniformly doped into the titanium niobium oxide bulk phase, with good uniformity, and is not prone to problems such as agglomeration and segregation, which is conducive to making the high-entropy doped titanium niobium oxide have better sodium storage performance, and when used as a sodium battery negative electrode material, it has a higher specific capacity, higher rate characteristics and better cycle performance.

[0044] According to an embodiment of the present application, M includes at least one element with a maximum valence state lower than +5 and at least one element with a maximum valence state higher than +5. As an example, elements with a maximum valence state higher than +5 include but are not limited to Mo, Re, W, etc., and elements with a maximum valence state lower than +5 include but are not limited to Mg, Cr, Ni, Cu, etc. Specifically, niobium element usually exists in the crystal structure of high entropy doped titanium niobium oxide in the form of +5 valence. The doping element M partially selects elements with a maximum valence state higher than +5 valence, and partially selects elements with a maximum valence state lower than +5 valence, which is beneficial to valence balance and the generation of vacancies in the crystal structure, and can effectively regulate the configuration of high entropy doping, thereby being more conducive to ion conduction.

[0045] According to an embodiment of the present application, the specific types of metal elements included in M ​​may be 5, 6, 7, 8, 9, and the like. The amounts of different types of metal elements in M ​​can be selected according to actual needs. As an example, M includes at least 5 elements in equal moles. Taking M as an example, which includes five metal elements a, b, c, d, and e, the 5 elements in equal moles refer to the molar ratio of a, b, c, d, and e elements being 1:1:1:1:1. In this way, the high entropy doping effect can be better achieved, the ion transport capacity of high entropy doped titanium niobium oxide can be better improved, and more high-activity sites can be provided, so that it can well meet the use requirements of sodium negative electrode materials.

[0046] According to an embodiment of the present application, the high entropy doped titanium niobium oxide further includes: a conductive polymer coating layer, wherein the conductive polymer coating layer is coated on at least a portion of the surface of the compound shown in Formula 1. It can be understood that the conductive polymer layer may only cover a portion of the surface of the compound shown in Formula 1, or may cover the entire surface of the compound shown in Formula 1, that is, the conductive polymer layer completely wraps the compound shown in Formula 1. As an example, the conductive polymer layer completely wraps the compound shown in Formula 1. Thus, by introducing a conductive polymer to coat the high entropy doped titanium niobium oxide, its electronic conductivity is effectively improved and a higher structural stability is achieved. When it is used as a sodium negative electrode material, high specific capacity, high rate characteristics and excellent cycle performance can be achieved.

[0047] According to an embodiment of the present application, the material of the conductive polymer coating layer includes at least one of polyaniline, polypyrrole, and poly (3,4-ethylenedioxythiophene). Therefore, the above polymer has good conductivity, which is beneficial to improve the electronic conductivity and structural stability of high entropy doped titanium niobium oxide, and the material source is wide, easy to obtain, and low in cost. At the same time, it is easy to form a film on the surface of the compound shown in Formula 1 and easy to process.

[0048] According to an embodiment of the present application, the coating layer has a thickness of 0.1 nm to 5 nm, such as 0.1 nm, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, etc. As an example, the coating layer may have a thickness of 2 nm. Within this thickness range, the electronic conductivity and structural stability can be improved without causing any adverse effects.

[0049] According to an embodiment of the present application, the mass percentage of carbon in the high entropy doped titanium niobium oxide is 0.2% to 0.8%, specifically 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, etc. As an example, the mass percentage of carbon in the coating layer can be 0.4%.

[0050] According to the embodiments of the present application, the high entropy doped titanium niobium oxide has a porous structure, which can greatly accelerate the transmission of sodium ions between particles and crystal domains, and can achieve better electrochemical performance when used as a negative electrode material for sodium ion batteries.

[0051] According to an embodiment of the present application, the porous structure includes mesopores with a pore size of 3nm to 10nm (specifically 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, etc.). Thus, the transmission of sodium ions between particles and crystal domains can be further accelerated, and better electrochemical performance can be achieved when used as a negative electrode material for sodium ion batteries.

[0052] According to the embodiment of the present application, the high entropy doped titanium niobium oxide is in the form of microspheres, and the D 50 The particle size is 4 μm to 15 μm, specifically 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc. It has a spherical morphology, which is more conducive to the transmission of sodium ions, and can achieve better electrochemical performance when used in the negative electrode material of sodium ion batteries.

[0053] In this paper, D 50The particle size has a well-known meaning in the art, which means the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T19077-2016. The test instrument can be the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK.

[0054] In a second aspect of the present application, a method for preparing the high entropy doped titanium niobium oxide described above is provided. According to an embodiment of the present application, the method comprises:

[0055] S1: Mix a carbon source, a titanium source, a niobium source, an M source and a solvent to obtain a mixed solution.

[0056] In this step, the specific operation method of mixing the carbon source, titanium source, niobium source, M source and solvent is not particularly limited, as long as the above raw materials can be mixed and mixed as uniformly as possible. In some embodiments, the carbon source, titanium source, niobium source and M source can be added to the solvent, and then stirred at a speed of 300 rpm until completely dissolved to obtain the mixed solution.

[0057] According to the embodiments of the present application, the ratio of the carbon source, titanium source, niobium source, and M source can be determined according to the specific composition of the high entropy doped titanium niobium oxide. In some embodiments, the mass ratio of the carbon source, titanium source, niobium source, and M source can be (0.01-10): (10-30): (400-600): (0.01-20), specifically (3-7): (15-25): (450-550): (5-15), for example 0:5:20:500:10, 3:15:450:5, 3:20:500:10:, 3:25:550:15, 5:20:500:10, 5:15:550:5, 7:25:450:15, and the like. Within the above-mentioned ratio range, high-entropy doped titanium niobium oxide has a structure that is more conducive to ion transport, can meet the requirements for use as a sodium ion negative electrode material, can be effectively used as a sodium ion negative electrode material, and can improve the performance of sodium ion batteries.

[0058] It can be understood that in this step, a carbon source may or may not be added, and the specific choice can be made according to actual needs. Specifically, the carbon source will be oxidized and removed in the calcination step, thereby forming a porous structure in the high-entropy doped titanium niobium oxide, which plays a key role in morphology and particle size regulation, introduction of pore structure, etc. According to an embodiment of the present application, the carbon source may include at least one of glucose, starch, sucrose, and fructose. Thus, it is conducive to the formation of a porous structure in the high-entropy doped titanium niobium oxide, and the material source is wide and the cost is low.

[0059] According to an embodiment of the present application, the titanium source may include at least one of tetrabutyl titanate and titanium isopropoxide. The niobium source may include at least one of niobium pentachloride and niobium ethoxide. The M source may include compounds of at least five elements of Re, Mo, W, V, Cr, Cu, Ni, Fe, Co, Cu, Zn, Mn, Sn, Bi, K, Mg, Al, Li, Rb, Cs, Ru, Rh, Pd, Ag, In, Ir, and Pb that are soluble in the solvent. Thus, the reaction is facilitated, the material is easily available, and the cost is low.

[0060] According to the embodiments of the present application, the solvent that can be used in this step is not particularly limited, as long as it can dissolve the raw materials well and ensure the smooth progress of the reaction. In some embodiments, the solvent includes ethanol.

[0061] S2: subjecting the mixed solution to a hydrothermal reaction to obtain an intermediate.

[0062] In this step, the mixed solution can be added into a reaction container (such as a reactor), and then the mixed solution is heated to allow the carbon source, titanium source, niobium source, and M source to react to obtain an intermediate.

[0063] According to the embodiments of the present application, the temperature of the hydrothermal reaction can be 100°C to 200°C, specifically 120°C to 180°C, more specifically 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc. Within the above temperature range, the hydrothermal reaction is suitable, the reaction is sufficient, the speed is fast, and there are few side reactions. If the temperature is too low, the reaction speed will decrease, which is not conducive to the full reaction or takes too long, and if the reaction temperature is too high, the side reactions may increase.

[0064] According to the embodiments of the present application, the heating rate of the hydrothermal reaction is 2°C / min to 20°C / min, specifically 5°C / min to 15°C / min, more specifically 2°C / min, 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min, 18°C / min, 20°C / min, etc. The above heating rate range can make the high entropy doped titanium niobium oxide have a suitable pore size and good uniformity of each doping element. If the heating rate is low, it may cause a more sufficient reaction in the low temperature section, reduce the pore size, or cause the doping elements to aggregate; if the heating rate is too fast, the equipment requirements will be more stringent, which is not conducive to preparation, and the cost may increase.

[0065] According to the embodiments of the present application, the holding time of the hydrothermal reaction is 0.2h-2h, specifically 0.2h-1h, more specifically 0.2h, 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, etc. The above time range allows the hydrothermal reaction to proceed fully without wasting time.

[0066] It can be understood that the mixture obtained after the hydrothermal reaction is completed, in order to obtain the intermediate, a separation operation needs to be performed. The specific separation operation is not particularly limited in this application and can be flexibly selected according to actual needs. For example, the intermediate can be obtained by filtering, washing, drying and other steps. In some embodiments, the mixture obtained after the hydrothermal reaction is naturally cooled to room temperature, taken out and filtered, and then washed and filtered alternately with water and anhydrous ethanol until the filtrate is clear and transparent, and the pH of the last drop of filtrate is close to 7, and the solid substance is placed in an oven at 80°C for drying to obtain a black solid powder, which is the intermediate.

[0067] S3: calcining the intermediate to obtain the compound represented by formula 1.

[0068] In this step, the intermediate can be placed in a crucible and calcined at a high temperature, so that the intermediate is converted into high-entropy doped titanium niobium oxide.

[0069] According to the embodiments of the present application, the temperature of the calcination treatment is 300°C to 1800°C, specifically 500°C to 1200°C, more specifically 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc. In the above temperature range, it is beneficial to obtain high-entropy doped titanium niobium oxide with a suitable porous structure and high-entropy doping configuration, thereby achieving better sodium ion transport performance.

[0070] According to the embodiments of the present application, the heating rate of the calcination treatment is 10°C / min to 200°C / min, specifically 10°C / min to 200°C / min, more specifically 10°C / min, 20°C / min, 30°C / min, 40°C / min, 50°C / min, 60°C / min, 70°C / min, 80°C / min, 90°C / min, 100°C / min, 110°C / min, 120°C / min, 130°C / min, 140°C / min, 150°C / min, 160°C / min, 170°C / min, 180°C / min, 190°C / min, 200°C / min, etc. Within the above heating rate range, it is beneficial to obtain high entropy doped titanium niobium oxide with good uniformity of doping elements. If the heating rate is too low, the doping elements may aggregate at the low temperature stage, and the uniformity of the doping elements is relatively poor. If the heating rate is too high, the reaction conditions are harsh, the equipment requirements are higher, and the cost may increase.

[0071] According to the embodiments of the present application, the holding time of the calcination treatment is 0.1h to 2h, specifically 0.3h to 1h, more specifically 0.1h, 0.2h, 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, etc. Within the above temperature range, the reaction can be fully carried out without wasting time due to too long a time, which is conducive to improving efficiency.

[0072] According to an embodiment of the present application, the method further includes:

[0073] S4: forming a conductive polymer coating layer on the surface of the compound represented by Formula 1.

[0074] According to the embodiments of the present application, the introduction of a conductive polymer to coat high-entropy doped titanium niobium oxide can effectively improve the electron conductivity and achieve higher structural stability. As a negative electrode material for sodium ion batteries, it can achieve higher specific capacity, higher rate characteristics and excellent cycle performance.

[0075] According to an embodiment of the present application, forming a conductive polymer coating layer may include: immersing the compound represented by Formula 1 in a conductive polymer monomer aqueous solution to obtain a dispersion; adding an initiator to the dispersion, and continuously stirring to polymerize the conductive polymer monomer to form the conductive polymer coating layer on the surface of the compound represented by Formula 1. Specifically, the conductive polymer monomer may undergo a polymerization reaction under the initiation of the initiator and be coated on the surface of the compound represented by Formula 1.

[0076] According to the embodiment of the present application, the concentration of the conductive polymer monomer aqueous solution is 0.1M to 1M, specifically 0.2M to 0.6M, more specifically 0.1M, 0.2M, 0.3M, 0.4M, 0.5M, 0.6M, etc. Thus, a conductive polymer coating layer with a better coating effect can be obtained, which can effectively improve the electronic conductivity and achieve higher structural stability. If the concentration is too high, excessive growth of the conductive polymer may occur, which is not conducive to the improvement of the electronic conductivity and the proportion of active substances, as well as the smoothness of the ion transport channel. If the concentration is too low, the coating effect may be poor, and the improvement effect on the electronic conductivity and structural stability is limited.

[0077] According to the embodiments of the present application, the polymerization reaction time is 0.5h to 2h, specifically 1h to 1.5h, for example, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h, etc. Within the above time range, a conductive polymer coating layer with better effect can be obtained.

[0078] It is understood that after the polymerization reaction is completed, a separation step is required to obtain the target product. In some embodiments, the mixture after the polymerization reaction is completed can be filtered and dried to obtain a high entropy doped titanium niobium oxide coated with a conductive polymer coating layer.

[0079] In a third aspect of the present application, a negative electrode material for a sodium ion battery is provided. According to an embodiment of the present application, the negative electrode material for a sodium ion battery comprises the high entropy doped titanium niobium oxide described above, or the high entropy doped titanium niobium oxide prepared by the method described above. Using high entropy doped titanium niobium oxide as a negative electrode material for a sodium ion battery can achieve high specific capacity, high rate characteristics and excellent cycle performance.

[0080] In a fourth aspect of the present application, a sodium ion battery is provided. According to an embodiment of the present application, the sodium ion battery comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode material, and the negative electrode material comprises the sodium ion battery negative electrode material described above. The sodium ion battery has a high specific capacity, a high rate characteristic and excellent cycle performance.

[0081] It can be understood that there is no particular limitation on the specific type of the sodium ion battery, which can be a primary battery or a secondary battery; the shape of the sodium ion battery can be a cylindrical battery, a square battery or a battery of any other shape, and according to the outer packaging classification, the sodium ion battery can be a hard shell battery, a soft pack battery, etc.

[0082] Typically, a sodium-ion battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by winding or lamination process, and the electrode assembly and the electrolyte can be contained in an outer package. During the charge and discharge process of the sodium-ion battery, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows ions to pass through.

[0083] The positive electrode sheet in the sodium ion battery may include a positive electrode current collector and a positive electrode material layer, wherein the positive electrode material layer is arranged on at least one surface of the positive electrode current collector.

[0084] In some embodiments, the positive electrode current collector may be a metal current collector or a composite current collector. For example, the metal current collector includes but is not limited to an aluminum foil current collector; the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0085] In some embodiments, the positive electrode material layer may include positive electrode active substances, binders and conductive agents, and additives with specific functions and effects may be added according to actual needs, such as thickeners, sodium supplements, film-forming additives, flame retardants, high temperature / low temperature stabilizers, etc.

[0086] As an example, the positive active material of the sodium ion battery may include one or more of a layered oxide, a polyanion compound, and a Prussian blue compound. For example, the layered oxide may include Na y M'O2, M'=Fe, Mn, Ni, Co, Cr, Sc, Ti, V, Cr, Cu, Zn and combinations thereof, 0.4≤y≤1, for example, NaVO2, NaFeO2, Na 0.7 CoO2、NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2、NaFe 0.5 Ni 0.5 O2、Na 0.6 MnO2、Na 0.44 MnO2、Na 0.65 Mn 0.75 Ni 0.25 O2、NaNi 0.5 Mn 0.5 O2、Na0.78 Ni 0.23 Mn 0.69 O2、Na 0.67 Mn 0.67 N i0.33 O2, etc. The polyanion compounds may include one or more of phosphate, pyrophosphate, sulfate type, anion doped type, such as olivine type NaFePO4, Na2FeP2O7, NaFePO4F, Na3V2(PO4)3, NaFeSO4. Prussian blue compounds may include Na 0.61 Fe[Fe(CN)6] 0.94 , BR-FeHCF, Na 1.48 Ni[Fe(CN)6] 0.89 、NaNi 0.05 Mn 0.95 [Fe(CN)6] or more.

[0087] As an example, the binder in the positive electrode active material layer may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin.

[0088] As an example, the conductive agent in the positive active material layer may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0089] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector.

[0090] As an example, the negative electrode active material layer may include a negative electrode active material, a thickener, a conductive agent and a binder, wherein the negative electrode current collector may be a metal foil, for example, the metal foil may be a copper foil. The negative electrode active material may include the high entropy doped titanium niobium oxide described above.

[0091] According to an embodiment of the present application, the binder in the negative electrode material layer may include butadiene styrene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and at least one of carboxymethyl chitosan (CMCS).

[0092] According to an embodiment of the present application, the conductive agent in the negative electrode material layer may include but is not limited to at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0093] In some embodiments, the separator can be a separator known in the art that can be used in sodium ion batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, etc.

[0094] In a fifth aspect of the present application, an electric device is provided. According to an embodiment of the present application, the electric device includes the sodium ion battery described above. The electric device has all the features and advantages of the sodium ion battery described above, which will not be described one by one here.

[0095] According to the embodiments of the present application, the specific type of the electrical device is not particularly limited, and can be any device that uses a sodium ion battery as a power source or energy storage unit. As an example, the electrical device includes but is not limited to electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), mobile terminals (such as mobile phones, laptops, game consoles, wearable devices, etc.), drones, aerospace equipment, satellites, ships, energy storage systems, etc. It can be understood that in addition to the batteries described above, the electrical device also includes necessary structures and components, all of which can be carried out with reference to conventional technologies, such as electric vehicles, which may include a body, chassis, tires, navigation systems, radar systems, steering systems, braking systems, lubrication systems, cooling systems, driving systems, etc., which will not be repeated here.

[0096] The embodiments of the present application are described in detail below.

[0097] Example 1

[0098] (1) Add a salt mixture of starch, tetrabutyl titanate, niobium ethoxide, ammonium rhenate, molybdenum pentachloride, nickelocene, anhydrous copper sulfate, and magnesium sulfate heptahydrate in a mass ratio of 5:20:480:5 into 70 mL of anhydrous ethanol, and stir at 300 rpm for 40 min until completely dissolved;

[0099] (2) The solution obtained in (1) was poured into a 100 mL reactor, the hydrothermal temperature was 150°C, the heating rate was 10°C / min, the holding time was 0.5 h, and then naturally cooled to room temperature, taken out and filtered, and washed and filtered alternately with water and anhydrous ethanol until the filtrate was clear and transparent, and the pH of the last drop of filtrate was close to 7, and the solid matter was placed in an oven at 80°C to dry to obtain a black solid powder;

[0100] (3) In an air environment, the powder obtained in (2) is evenly spread in a crucible and subjected to high-temperature calcination treatment, with a maximum temperature of 800°C, a heating rate of 160°C / min, and a holding time of 0.5h, and then naturally cooled to room temperature to obtain a high-entropy doped titanium niobium oxide material;

[0101] (4) The high entropy doped titanium niobium oxide material obtained in (3) was immersed in a 0.3 M pyrrole aqueous solution, and after being evenly dispersed by stirring at a speed of 300 rpm, 0.1 M ammonium persulfate solution was slowly added dropwise, and stirring was continued for 1 hour. Then, the material was taken out and filtered, and washed and filtered alternately with water and anhydrous ethanol until the filtrate was clear and transparent, and the pH of the last drop of filtrate was close to 7. The solid material was placed in an oven at 80°C for drying to obtain a polymer-coated high entropy doped titanium niobium oxide material.

[0102] The high entropy doped titanium niobium oxide material obtained in this example has a microspherical morphology (SEM photo as shown in Figure 1 ), D of microspheres 50 The particle size is mostly 6 μm, and the pores obtained by gas adsorption and desorption tests are mostly mesopores with a range of 3 nm to 10 nm.

[0103] Example 2

[0104] Same as Example 1, except that a salt mixture of starch, tetrabutyl titanate, niobium ethoxide, ammonium rhenate, molybdenum pentachloride, nickelocene, anhydrous copper sulfate, and magnesium sulfate heptahydrate was added into 70 mL of anhydrous ethanol at a mass ratio of 5:20:480:10, and stirred at 300 rpm for 40 min until completely dissolved.

[0105] Example 3

[0106] Same as Example 1, except that a salt mixture of starch, tetrabutyl titanate, niobium ethoxide, zinc acetate, nickelocene, anhydrous copper sulfate, magnesium sulfate heptahydrate, and potassium acetate was added into 70 mL of anhydrous ethanol at a mass ratio of 5:20:480:5, and stirred at 300 rpm for 40 min until completely dissolved.

[0107] Example 4

[0108] Same as Example 1, except that the heating rate in the hydrothermal reaction step is 2°C / min.

[0109] Example 5

[0110] Same as Example 1, except that the heating rate in the calcination step is 10°C / min.

[0111] Example 6

[0112] Same as Example 1, except that the maximum temperature in the calcination step is 1200°C.

[0113] Example 7

[0114] Same as Example 1, except that the concentration of the pyrrole aqueous solution is 0.6M.

[0115] Example 8

[0116] The same as Example 1, except that a salt mixture of tetrabutyl titanate, niobium ethoxide, ammonium rhenate, molybdenum pentachloride, nickelocene, anhydrous copper sulfate, and magnesium sulfate heptahydrate is added into 70 mL of anhydrous ethanol at a mass ratio of 20:480:5, and stirred at 300 rpm for 40 min until completely dissolved.

[0117] Example 9

[0118] Same as Example 1, except that the polymer coating in step (4) is not performed.

[0119] Comparative Example 1

[0120] Same as Example 1, except that starch, tetrabutyl titanate and niobium ethoxide are added into 70 mL of anhydrous ethanol at a mass ratio of 5:20:480, and stirred at 300 rpm for 40 min until they are completely dissolved.

[0121] Performance testing:

[0122] 1. Element ratio test: Use inductively coupled plasma atomic emission spectrometry (ICP-OES) to determine the metal element ratio. The specific test steps are as follows: decompose / digest the sample to dissolve the metal elements into a clear liquid; the sample to be tested is formed into an aerosol through a nebulizer, and the light radiated by the light source is heated and excited, and the light intensity is converted into photocurrent, which is processed by the circuit and calculated as the element content.

[0123] The mass percentage of carbon content is determined using an organic element analyzer. The specific test steps are as follows: the high-entropy doped titanium niobium oxide coated with a conductive polymer is placed in a high-temperature oxygen environment to burn the organic matter to obtain gaseous oxides of different elements, which are separated and detected through a chromatographic column to obtain the mass percentage of carbon.

[0124] 2. Pore volume and pore size distribution test: Use a nitrogen adsorption-desorption instrument to perform nitrogen adsorption-desorption test on the sample, obtain the adsorption-desorption curve, and calculate the pore volume and pore size distribution results.

[0125] 3. Battery performance test: The materials obtained in Examples 1 to 9 and Comparative Example 1 were used as negative electrode active materials, respectively, and negative electrode sheets were prepared with a formula of negative electrode active material: CMC: SBR: SP = 100: 1.5: 3: 1. The sodium sheet was used as the positive electrode. The electrolyte used 1M NaPF6 / (the volume ratio of EC and DMC was 1: 1), the diaphragm used glass fiber, and the button half-cell was assembled in a glove box filled with high-purity argon. The electrochemical performance was carried out on a Wuhan Blue Electric CT2001A battery tester, the charge and discharge voltage range was controlled at 0-3V, and the charge and discharge current density was 50, 100, 200, 500, 1000, 2000mA / g respectively. The test results are summarized in Table 2.

[0126] Table 1: Element proportion test results

[0127]

[0128]

[0129] As shown in Table 1, in each embodiment and comparative example, the atomic ratio of Ti, Nb and O is very close to 1:24:62, indicating that TiNb was successfully prepared. 24 O 62 . In Example 1, the atomic proportion of each doping element Re\Mo\Ni\Cu\Mg is 0.2%, indicating that uniform doping of each element is achieved. Since the relative proportion of Ti and Nb atoms is slightly higher than 1:24, it is speculated that each doping element randomly replaces the position of niobium atoms. Through elemental analysis, it is determined that the coating amount of polypyrrole is about 0.5wt.%, and the mass ratio of carbon / nitrogen is close to 4:1, indicating that the coating is polypyrrole.

[0130] Compared with Example 1, the feeding ratio of the mixed metal salt in Example 2 is increased. Due to the increase in concentration, the uniformity of the raw materials is slightly reduced.

[0131] Compared with Example 1, after the M source is adjusted to Zn\Ni\Cu\Mg\K in Example 3, the proportion of each metal atom is 0.2%, indicating that uniform doping can still be achieved using different mixed metal sources.

[0132] Compared with Example 1, in Example 4, the hydrothermal heating rate is reduced to 2°C / min. The slower hydrothermal heating rate leads to a more sufficient reaction in the low-temperature section. On the one hand, it causes the pore size of the porous microspheres to decrease (to 2-7 nm). On the other hand, it causes the atomic proportions of each doping element Re\Mo\Ni\Cu\Mg to deviate significantly from 0.2%, indicating that the rapid heating of the hydrothermal process is conducive to reducing the possibility of element aggregation in the low-temperature process and achieving uniform dispersion of mixed metal elements.

[0133] Compared with Example 1, in Example 5, the heat treatment heating rate is reduced to 10°C / min. The slower heat treatment heating rate causes the atomic proportions of each doping element Re\Mo\Ni\Cu\Mg to deviate significantly from 0.2%, indicating that the rapid heating process of the heat treatment is more conducive to reducing the possibility of element aggregation during the low-temperature process and achieving uniform dispersion of mixed metal elements.

[0134] Compared with Example 1, no carbon source was added in Example 8, and the SEM photos are as follows Figure 2As shown, the particles are in irregular block shape and have a relatively large particle size (mostly 7-9μm). There are no obvious differences on the particle surface, indicating that the particles have less porous structure, which shows that the carbon source plays a key role in spheroidization, particle size regulation and introduction of porous structure. The atomic proportion of each metal element Re\Mo\Ni\Cu\Mg deviates from 0.2%, indicating that the presence of the carbon source is conducive to the uniform dispersion of metal elements in the precursor. The proportion of carbon and nitrogen elements is reduced to 0.36wt.%, indicating that the larger particle size and non-porous structure lead to a decrease in the coating sites of polypyrrole and a decrease in the coating amount.

[0135] Compared with Example 1, the polymer coating in step (4) was not performed in Example 9, so the carbon and nitrogen content in the obtained material was 0.

[0136] Compared with Example 1, no mixed metal salt was added in Comparative Example 1 to obtain TiNb 24 O 62 The element ratio of Ti, Nb and O is 1:24:62, indicating that pure phase TiNb was synthesized. 24 O 62 .

[0137] Table 2: Battery performance test results

[0138]

[0139] It can be seen from Table 2 that the polymer-coated high-entropy doped TiNb in the embodiment of the present application 24 O 62 The material has an initial reversible capacity at a current density of 50 mA / g, an initial coulombic efficiency, a reversible capacity at a current density of 2000 mA / g of 328.6 mA h / g, and a capacity retention rate of 92.3% after 4000 cycles at a current density of 500 mA / g, all of which are better than comparative example 1. It is explained that the high entropy structure of the high-entropy doped titanium-niobium compound of the present application helps to increase the interlayer spacing, regulate the band structure, introduce oxygen vacancies, etc., improve the capacity and kinetic performance, and the rich pore structure is conducive to ion transport and improves the rate performance; and the conductive polymer coating can help to improve the electron conduction ability.

[0140] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0141] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A high entropy doped titanium niobium oxide, characterized in that: Including the compound shown in formula 1: TnB 24-x M x O 62 Formula 1 Wherein, M includes at least 5 of Re, Mo, W, V, Cr, Cu, Ni, Fe, Co, Cu, Zn, Mn, Sn, Bi, K, Mg, Al, Li, Rb, Cs, Ru, Rh, Pd, Ag, In, Ir and Pb; x is 0.8 to 1.

6.

2. The high entropy doped titanium niobium oxide according to claim 1, characterized in that: M includes at least one element having a highest valence state lower than +5 and at least one element having a highest valence state higher than +5.

3. The high entropy doped titanium niobium oxide according to claim 1 or 2, characterized in that: M includes at least 5 elements in equimolar amounts.

4. The high entropy doped titanium niobium oxide according to claim 1, characterized in that: x is 0.9 to 1.

2.

5. The high entropy doped titanium niobium oxide according to claim 1, characterized in that: Also includes: A conductive polymer coating layer is coated on at least a portion of the surface of the compound represented by Formula 1.

6. The high entropy doped titanium niobium oxide according to claim 5, characterized in that: The material of the conductive polymer coating layer includes at least one of polyaniline, polypyrrole and poly (3,4-ethylenedioxythiophene).

7. The high entropy doped titanium niobium oxide according to claim 5, characterized in that: Satisfy at least one of the following conditions: The thickness of the coating layer is 0.1 nm to 5 nm, preferably 2 nm; In the high entropy doped titanium niobium oxide, the mass proportion of carbon element is 0.2% to 0.8%, preferably 0.4%.

8. The high entropy doped titanium niobium oxide according to claim 1, characterized in that: The high entropy doped titanium niobium oxide has a porous structure and satisfies at least one of the following conditions: The porous structure includes mesopores with a pore size of 3nm to 10nm; The pore volume of the porous structure is 0.01 g / cm 3 ~0.6g / cm 3 , preferably 0.03 g / cm 3 .

9. The high entropy doped titanium niobium oxide according to claim 1, characterized in that: The high entropy doped titanium niobium oxide is in the shape of microspheres, and the D50 particle size of the microspheres is 4 μm to 15 μm.

10. A method for preparing the high entropy doped titanium niobium oxide according to any one of claims 1 to 9, characterized in that: include: Mixing a carbon source, a titanium source, a niobium source, an M source and a solvent to obtain a mixed solution; subjecting the mixed solution to a hydrothermal reaction to obtain an intermediate; The intermediate is calcined to obtain the compound shown in Formula 1.

11. The method according to claim 10, characterized in that Satisfy at least one of the following conditions: The mass ratio of the carbon source, titanium source, niobium source and M source is (0.01-10): (10-30): (400-600): (0.01-20), preferably (3-7): (15-25): (450-550): (5-15); The carbon source includes at least one of glucose, starch, sucrose and fructose; The titanium source includes at least one of tetrabutyl titanate and titanium isopropoxide; The niobium source includes at least one of niobium pentachloride and niobium ethoxide; The M source includes compounds of at least five elements of Re, Mo, W, V, Cr, Cu, Ni, Fe, Co, Cu, Zn, Mn, Sn, Bi, K, Mg, Al, Li, Rb, Cs, Ru, Rh, Pd, Ag, In, Ir, and Pb that are soluble in the solvent; The solvent includes ethanol.

12. The method according to claim 10, characterized in that The hydrothermal reaction satisfies at least one of the following conditions: The temperature of the hydrothermal reaction is 100°C to 200°C, preferably 120°C to 180°C; The heating rate of the hydrothermal reaction is 2°C / min to 20°C / min, preferably 5°C / min to 15°C / min; The holding time of the hydrothermal reaction is 0.2h to 2h, preferably 0.2h to 1h.

13. The method according to claim 10, characterized in that The calcination treatment satisfies at least one of the following conditions: The calcination temperature is 300°C to 1800°C, preferably 500°C to 1200°C; The heating rate of the calcination treatment is 10°C / min to 200°C / min, preferably 10°C / min to 200°C / min; The holding time of the calcination treatment is 0.1h to 2h, preferably 0.3h to 1h.

14. The method according to any one of claims 10 to 13, characterized in that: Also includes: A conductive polymer coating layer is formed on the surface of the compound represented by Formula 1.

15. The method according to claim 14, characterized in that Forming the conductive polymer coating layer comprises: Immersing the compound represented by Formula 1 into an aqueous solution of a conductive polymer monomer to obtain a dispersion; An initiator is added to the dispersion, and the mixture is continuously stirred to allow the conductive polymer monomer to undergo a polymerization reaction, so as to form the conductive polymer coating layer on the surface of the compound represented by Formula 1.

16. The method according to claim 15, characterized in that Meet at least one of the following conditions: The concentration of the conductive polymer monomer aqueous solution is 0.1M to 1M, preferably 0.2M to 0.6M; The polymerization reaction time is 0.5 h to 2 h, preferably 1 h to 1.5 h.

17. A negative electrode material for a sodium ion battery, characterized in that: The invention comprises the high entropy doped titanium niobium oxide according to any one of claims 1 to 9, or the high entropy doped titanium niobium oxide prepared by the method according to any one of claims 10 to 16.

18. A sodium ion battery, characterized in that: It comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode material, and the negative electrode material comprises the sodium ion battery negative electrode material according to claim 17.

19. An electrical device, characterized in that: Including the sodium ion battery as described in claim 18.

Citation Information

Patent Citations

  • Modified niobium-titanium oxide and preparation method and application thereof

    CN111725493A

  • Molybdenum-vanadium-titanium-niobium composite oxide negative electrode material, preparation method thereof and lithium ion battery

    CN114388772A

  • High-entropy doped lithium ferric manganese phosphate positive electrode material with hierarchical pore structure and preparation method of high-entropy doped lithium ferric manganese phosphate positive electrode material

    CN117038909A

  • Titanium niobate material, preparation method thereof and battery

    CN118145705A

  • Doped titanium niobate and battery

    US20200140339A1